Assessing the impact of environmental regulation on industrial water use: Evidence from Brazil - José Féres; Arnaud Reynaud (Institute for Applied Economic Research (ipea), 2015)
This paper aims at characterizing water demand by Brazilian manufacturing plants located in S\~ao Paulo and at assessing the potential impacts of environmental policies on industrial water use. We first show that the price elasticity of the water demand, -1.0 on average, is high enough for a water charge to act as an effective policy tool for reducing water consumption. Results also provide some evidence of a tradeoff between water quality improvement and water conservation policies, since more stringent environmental standards may lead to a higher water demand. A joint use of environmental norms and water charges may reconcile both policy goals.
Keywords: Q21; Q25; L5; 330